Co-producing a live fieldwork broadcast in the biosciences - Janine Maddison; Leah Ada Constantinou; Ellen Fletcher; Callum Turner; Richard Bevan; Sara Marsham (Frontiers in Education)
Most live broadcast work in education operates with an expert to novice delivery mode, and in indoor settings such as surgical teaching environments. Those few examples of live broadcasts from outdoor locations have heavy resource requirements, limiting their uptake within Higher Education. Working with undergraduates in a students as partners approach, this research aims to test the feasibility of a low-cost and low-tech solution to co-produce a live fieldwork broadcast within the biosciences. The co-production partnership successfully produced a live broadcast from conception to delivery in 2022–2023 with three placement students and in 2023–2024 with two placement students and three mentors. The students were involved in all aspects of design, development, and delivery of the live fieldwork broadcast. A pocket wireless modem creates an outdoor wireless network with a mobile device and wireless microphones used to deliver the broadcast. Semi-structured interviews, student self-assessments, and a reflective researcher diary explored the impact of this approach to co-produce a live fieldwork broadcast. Enjoyable aspects of the placement identified were the opportunity for new experiences and a sense of achievement. The live fieldwork broadcast placement enabled the placement students to develop 28 skills, with 73% of skills identified by at least two of the placement students. Most skills developed were transferable (54% of student identified skills), including teamwork and project planning. The simple and low-cost technology used provides a solution to address the barriers of technology integration within fieldwork and offers insight into the experience of working in partnership during a live fieldwork broadcast.